2011
DOI: 10.1891/0889-8391.25.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Three Anxiety Disorder Cases With Acceptance and Commitment Therapy in a Private Practice

Abstract: Acceptance and commitment therapy (ACT) for anxiety disorders is a type of cognitive behavioral therapy that focuses on decreasing the behavior regulatory function of anxiety and related cognitions, and has a strong focus on behavior change that is consistent with client values. In this case series, 3 consecutive referrals seeking treatment for anxiety disorders at a private practice were treated with 9-13 sessions of ACT. In-session exposure therapy was not included to determine the effects of ACT without the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Over the past several years, a growing body of research has demonstrated that ACT is effective in treating individuals with a wide range of behavioral and health issues, including depression, anxiety, substance use problems, smoking, diabetes, chronic pain, epilepsy, and work-related stress (Hayes, Luoma, Bond, Masuda, & Lillis, 2006). Specifically, there has been a great deal of research demonstrating ACT's efficacy in treating anxiety (Arch & Craske, 2008;Codd, Twohig, Crosby, & Enno, 2011;Eifert et al, 2009;Roemer & Orsillo, 2007;Roemer, Orsillo, & Salters-Pedneault, 2008). The ACT model of anxiety disorders proposes that attempts at regulating anxiety are at the core of anxiety disorders rather than the presence of particular levels of anxiety (Codd et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past several years, a growing body of research has demonstrated that ACT is effective in treating individuals with a wide range of behavioral and health issues, including depression, anxiety, substance use problems, smoking, diabetes, chronic pain, epilepsy, and work-related stress (Hayes, Luoma, Bond, Masuda, & Lillis, 2006). Specifically, there has been a great deal of research demonstrating ACT's efficacy in treating anxiety (Arch & Craske, 2008;Codd, Twohig, Crosby, & Enno, 2011;Eifert et al, 2009;Roemer & Orsillo, 2007;Roemer, Orsillo, & Salters-Pedneault, 2008). The ACT model of anxiety disorders proposes that attempts at regulating anxiety are at the core of anxiety disorders rather than the presence of particular levels of anxiety (Codd et al, 2011).…”
mentioning
confidence: 99%
“…Specifically, there has been a great deal of research demonstrating ACT's efficacy in treating anxiety (Arch & Craske, 2008;Codd, Twohig, Crosby, & Enno, 2011;Eifert et al, 2009;Roemer & Orsillo, 2007;Roemer, Orsillo, & Salters-Pedneault, 2008). The ACT model of anxiety disorders proposes that attempts at regulating anxiety are at the core of anxiety disorders rather than the presence of particular levels of anxiety (Codd et al, 2011). Thus, ACT aims to decrease avoidance of these inner experiences as the dominant response to anxiety (Codd et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Four case studies have shown preliminary support for the use of ACT as a treatment of PTSD in adults (Codd, Twohig, Crosby, & Enno, 2011;Orsillo & Batten, 2005;Twohig, 2009) and late-adolescence/young-adulthood (Batten & Hayes, 2005). Further, given the central role of emotional avoidance in individuals with PTS and PTSD, ACT theoretically makes sense as a treatment for PTS (Walser & Hayes, 2006).…”
Section: Trauma-focused Cognitive Behavioral Therapy (Tf-cbt) Is the mentioning
confidence: 98%
“…To date, no large studies have been conducted on ACT to treat PTSD, but four case studies have shown preliminary support for the use of ACT as a treatment for PTSD in adults (Codd et al, 2011;Orsillo & Batten, 2005;Twohig, 2009) and in late adolescence/early adulthood (Batten & Hayes, 2005). Further, a substantial amount of data supports the relationship between ACT processes and PTSD symptoms.…”
Section: Act and Ptsdmentioning
confidence: 99%